Treatment outcomes and prognostic factors in external auditory canal squamous cell carcinoma - Byung Chul Kang; Se Eun Yi; Woo Seok Kang; Joong Ho Ahn; Hong Ju Park; Jong Woo Chung (PLoS ONE, 2025)
External auditory canal carcinoma (EACC) is a rare and aggressive malignancy with substantial variability in prognosis depending on tumor stage and adjacent structure involvement. We retrospectively reviewed 56 patients with histologically confirmed squamous cell carcinoma of the external auditory canal treated at a tertiary referral center between 2000 and 2022. Clinical data including demographics, tumor stage, treatment modalities, surgical approach, and survival outcomes were analyzed. Kaplan–Meier survival curves and Cox proportional hazards regression were used to identify prognostic factors for overall survival (OS) and disease-specific survival (DSS). Of the 56 patients (mean age 61.6 years; 46.4% female), 30 had early-stage (T1–T2) and 26 had advanced-stage (T3–T4) tumors. The 5-year OS rates were 100.0% for early-stage, 60.0% for T3, and 42.0% for T4 disease. Advanced T-stage, nodal metastasis, and abutment to vascular structures such as the carotid artery or jugular bulb were significantly associated with worse outcomes. In multivariate analysis, younger age, vascular abutment, and nodal metastasis were independent negative prognostic factors. En bloc resection with clear margins was associated with improved survival. These findings emphasize the importance of early diagnosis and meticulous surgical planning to achieve complete resection and optimize outcomes in patients with EACC.